THE RELIABILITY OF THE TEST “BUNNY JUMPS FORWARD” - Edis Begatović; Ivan Čuk; Almir Atiković (Sport Scientific And Practical Aspects, 2025)
In this paper we designed a new composite test and we named it “bunny-jumps forward”. We decided to check the reliability as a metric characteristic of the test. We had two tests 1. the test to check the lap time for nine meters and 2. the test to check the frequency of jumps (the number of jumps) for nine meters. Only for that purpose a special nine-meter long drilling area is arranged for measuring bunny-jumps forward which is calibrated with yellow and red cones that are separated 50 cm from one another. Brower Timing System consists of one pair of photocells which are placed along nine meters of the drilling area and they make contacts with one another. Every pair of photocells is placed near the runway so that when the examinee passes, the photocells transmit the signal to the transmitter which at the same time receives the data and memorizes it in internal memory, which can later be used for further analysis and research. Two tests were used and each of them was repeated two times. The test proved high level of reliability. Other metric characteristics should be used on the same population in the further research so that the results could be compared and the reliability of the newly-designed composite test could be ascertained.